Meta-analysis of Jelajah Alam Sekitar (JAS) Approach Implementation in Learning Procces - Ngabekti, S.; Ridlo, S.; Peniati, E.; Martanto, R. (Jurnal Pendidikan IPA Indonesia, 2017)
The results of tracer studies on the approach of Jelajah Alam Sekitar (JAS) or environment exploring learning has been detected is used in eight provinces in Indonesia and studied in the learning begin primary school to college. Then, how the effectiveness of the implementation of the JAS approach in improving the learning process. This study uses meta-analysis-data in the form of descriptive exploratory qualitative. Data was taken from the various thesis, and research faculty in the last 10 years. Data analysis was performed by calculating the percentage of the same findings for similar problems. The results showed a wide range of studies using different methods and approach such as qualitative descriptive, quasi-experimental, PTK and R and D to produce evidence that the approach JAS effective when applied in teaching, especially teaching biology in a variety of teaching materials. Various studies have shown the approach JAS managed to increase learning outcomes, can differentiate learning outcomes between treatment and control groups in which the treatment group had a mean score higher. Models/strategies/methods centered learning students are very relevant to implementation approach JAS making it seem more real, like a model of cooperative learning, think pair share, strategy role-playing, the investigation group, learning cycle 5e, hands-on activity, and so on, making it possible to continuously assessed and developed in the paradigm of competency-based curriculum developed.